ANALISIS PERSONAL BRANDING FASHION BLOGGER DIANA RIKASARI - Amanda Vivi Imawati; Ayu Wahyuni Solihah; Mohammad Shihab (Universitas Tribhuwana Tunggadewi, 2016)
Abstract: Personal branding is a way for people to build a brand about themselves. Diana Rikasari is an example of successful personal branding on the internet through her blog